EJ12 girl hero: hot and cold - MCFARLANE, SUSANNAH; SUSANNAH MCFARLANE (New York Scholastic, 2010)
introduces 10-year-old Emma Jacks, who balances being a normal schoolgirl$1 (Bdealing with a mean classmate, Nema$1 (Bwith her secret life as EJ12, a top agent for the SHINE agency.s
Keywords: balances the challenges of school life with her secret identity as a top agent for the SHINE agency; ike facing down bullies - becomes easier after a mission from SHINE agency